Plant Peroxisomes: A Factory of Reactive Species - Corpas, Francisco J.; González-Gordo, Salvador; Palma, José M. (Frontiers in Plant Science, 2020)
Plant peroxisomes are organelles with a single membrane which have the capacity to adapt their biochemical composition depending on the plant tissue, developmental stage as well as internal and external cellular stimuli. Besides the peroxisomal metabolism of reactive oxygen species (ROS) known several decades ago, in recent years new molecules with signaling potentiality have been found in these organelles, including nitric oxide (NO) and hydrogen sulfide (H2S). These molecules have generated a family of derived molecules designated as reactive nitrogen and sulfur species (RNS and RSS, respectively) which have the peculiarity/ability of regulating the own peroxisomal metabolism throughout posttranslational modifications such as S-nitrosation, nitration and persulfidation. Additionally, the peroxisomal metabolism of all these reactive species is also susceptible to be modified in response to external stimuli since they can be used as weapons against pathogens. This review has the aim to provide an update of the cross-talk of these families of reactive species within the own peroxisomes and with its cellular environment due to the recognized signaling properties of H2O2, NO and H2S.